Endovascular Therapy of M2 Occlusion in IMS III: Role of M2 Segment Definition and Location on Clinical and Revascularization Outcomes - Tomsick, T.A. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Uncertainty persists regarding the safety and efficacy of endovascular therapy of M2 occlusions following IV tPA. We reviewed the impact of revascularization on clinical outcomes in 83 patients with M2 occlusions in the Interventional Management of Stroke III trial according to specific M1-M2 segment anatomic features. MATERIALS AND METHODS: Perfusion of any M2 branch distinguished M2-versus-M1 occlusion. Prespecified modified TICI and arterial occlusive lesion revascularization and clinical mRS 0–2 end points at 90 days for endovascular therapy–treated M2 occlusions were analyzed. Post hoc analyses of the relationship of outcomes to multiple baseline angiographic M2 and M1 subgroup characteristics were performed. RESULTS: Of 83 participants with M2 occlusion who underwent endovascular therapy, 41.0% achieved mRS 0–2 at 90 days, including 46.6% with modified TICI 2–3 reperfusion compared with 26.1% with modified TICI 0–1 reperfusion (risk difference, 20.6%; 95% CI, −1.4%–42.5%). mRS 0–2 outcome was associated with reperfusion for M2 trunk (n = 9) or M2 division (n = 42) occlusions, but not for M2 branch occlusions (n = 28). Of participants with trunk and division occlusions, 63.2% with modified TICI 2a and 42.9% with modified TICI 2b reperfusion achieved mRS 0–2 outcomes; mRS 0–2 outcomes for M2 trunk occlusions (33%) did not differ from distal (38.2%) and proximal (26.9%) M1 occlusions. CONCLUSIONS: mRS 0–2 at 90 days was dependent on reperfusion for M2 trunk but not for M2 branch occlusions. For M2 division occlusions, good outcome with modified TICI 2b reperfusion did not differ from that in modified TICI 2a. M2 segment definition and occlusion location may contribute to differences in revascularization and good outcome between Interventional Management of Stroke III and other endovascular therapy studies.